OCB-Work-Family Facilitation: Is It Positive for All Attachment Orientations? - Reizer, Abira; Koslowsky, Meni; Friedman, Batel (Frontiers in Psychology, 2020)
The present study seeks to expand on research concerning the benefits of organizational citizenship behaviors (OCB) to work-family facilitation (WFF) by integrating the theoretical framework of the attachment personality perspective (Bowlby, 1982). We hypothesized that OCB would enhance WFF for employees having lower levels of avoidance and anxious orientations but reduce WFF for employees with higher levels of avoidance and anxiety orientations. Two studies were conducted to test these hypotheses. Study 1 adopted a cross-sectional design, and Study 2 implemented a diary procedure. In Study 1, employees from a pharmaceutical company completed attachment orientations and WFF questionnaires, whereas their direct supervisors assessed the participants’ OCB. In Study 2, attachment orientations of 108 participants were assessed, with OCB and WFF measures collected over 10 days. Findings from both studies supported our hypotheses relating to avoidance orientations. Performing OCB can enhance WFF, with the effect stronger for employees having lower avoidance orientations. However, findings regarding anxiety orientations were non-significant. A better understanding of the role that attachment orientations play in the OCB - WFF association may facilitate implementing possible interventions that could benefit both the organization and the family.